THE INFLUENCE OF DHIKR ON STUDENTS' EMOTIONAL INTELLIGENCE - Diva Rania Azzahra; Fatima Hannani Rambe; Putri Maharani; Renda Trinanda Nurbaiti (Journal of Psychology and Social Sciences, 2023)
Emotional intelligence is a person's ability to motivate oneself, control feelings of frustration, not be lulled by pleasure, control impulses, be able to manage so that stress does not paralyze the ability to think, and empathize. This study aims to provide an overview of emotional intelligence in students of by providing interventions in the form of dhikr therapy. The subjects of this study consisted of 30 students of . This research method is experimental research with pre-test, post-test, and follow up in one group. Based on output table “Paired Sample Test" above, it is known that the value of Sig. (2-tailed) is 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is an average difference between the results of the pre-test and post-test, which means that there is an influence between the application of dhikr in increasing emotional intelligence for students of .